The Contribution of Religious Orientation of Nahdlatul Ulama in Arabic Learning - Rizka Eliyana Maslihah (Indonesian Journal of Arabic Studies, 2022)
Referring to the history, Islam has various religious organizations, where each organization has its own orientation. And then the difference in philosophical background will influence the differences in educational objectives. This study was designed using qualitative methods and using a case study approach. The results of this study can be summarized as follows, (1). Religious orientations provide a clear contribution to the teaching method of material. These contributions appear on the following matters: (a). The material in the book Al-'Arobiyah Lin-Nasyiin in accordance with the religious orientation of Nahdlatul Ulama (NU) described in detail, as well as associated with extensive material in terms of religious orientation, habits, culture and NU motto. (b). The material in the book translated into Indonesian. (c). The teacher directs students to discuss in detail the material in the book are not in accordance with the orientation of the community organizations. (2). Religious orientations provide a clear contribution to the selection of teachers. These contributions appear on the following matters: (a). The main criteria in the selection of teachers is a teacher must hold fast to the orientation of NU organizations, and the school does not accept the teachers who do not hold on the organizations for keep the originality of the organization. (b). The teachers should have morality, in accordance with the provisions of the character. (c). The teachers must be master of the subject matter. (d). Each teacher must understand the orientation of community organizations followed. (e). Every teacher should be left active in the organization. (f). The schools prefer the alumni.